Decaffeinated green tea and green coffee extracts as metformin’s add-on enhance metabolic syndrome risk factors and improve the cardiac insulin-gene-related pathway - Indah Nur Chomsy; Mohammad Saifur Rohman; Husnul Khotimah; Nashi Widodo; Nur Ida Panca Nugrahini (Journal of Pharmacy & Pharmacognosy Research, 2023)
Context: Dysregulation of glucose metabolism in metabolic syndrome (METS) is allegedly due to the disruption of insulin as the main pathway in cellular metabolism. Green tea and green coffee are known to have potential benefit in METS therapy.